Meningkatkan Aktivitas Hasil Belajar Siswa Dan Keterampilan Berpikir Kritis Muatan IPS Menggunakan Model Barikit - Alfian Noor; Ari Hidayat (CV. ITTC INDONESIA, 2023)
The problem of this research is the resultant activity of low student learning and student capability in critical thinking for social studies content. This is due to the lack of participation from students at an active level at the learning stage and not so interesting. The solution to solve this problem is to implement learning using a model in the form of BARIKIT. The purpose of this study is to describe the activities of the teacher and analyze the activities of students, the results of learning and the ability to use critical thinking in social studies content Theme 7 Beautiful Diversity in My Country using the BARIKIT model in class IV SDN 3Pulau Kupang KualaKapuas. The approach of the research is a qualitative approach, the type of research used is classroom action research (PTK) which is carried out with a total of 4 meetings, implemented in class IV SDN 3 Pulau Kupang Kuala Kapuas with a total of 13 female students totaling 6 people and men there are 7 people. Techniques in collecting data used are tests and observations. Analysis of the data is descriptive analysis. The parameters of the success of student activities score 21-24 and skills using critical thinking score 13-16 which classically ≥80% and also the resultant of individual learning of all students who ≥65 KKM using classically ≥80%. The results showed that the teacher's activities in each of the 4 meetings obtained a score of 27 which the criteria was